Digital and Financial Access: Evidence from Household Consumption in Indonesia - Besti Novianda; Indah Maya Sari; Verni Juita (Equity: Jurnal Ekonomi, 2023)
This research focuses on the influence of formal finance access and digital financial services on household consumption in Indonesia. Researchers use secondary data by digging into information obtained from Susenas 2019 and using The Ordinary Least Square (OLS) method. The research results show that the development of Access to formal finance and digital financial services is increasingly developing, which will increase household consumption in Indonesia. The results of this study are based on previous studies. The results imply that digital financial inclusion can increase household consumption expenditure in Indonesia. It is important for policymakers to find the right mechanism to improve the financial well-being of Indonesia's economically vulnerable population. Promoting the comprehensive and balanced development of financial institutions is an important step to stimulate household consumption. Therefore, financial institutions need to embrace digital finance as a great opportunity and expand their market by providing easier access to financial services for low- and middle-income households so that people can reap the desired benefit.